”Creations of the professor’s fertile mind” – August Hagen’s artists’ novels - Christine Hübner (Journal of Art Historiography, 2020)
August Hagen (1798–1889), professor for history of art and aesthetics at the Prussian university of Königsberg, is the author of a series of historical novels on the subject of artists’ lives. Pretending to be transliterations of newly discovered or translated historical sources, Hagen re-wrote and novelized the lives of artists from the fifteenth and sixteenth century, enriching them with elements of light fiction. This paper focuses on the question of how Hagen’s novels were written, read and reviewed in a period marked by the development of history of art as an academic discipline.